2016
DOI: 10.1111/jre.12416
|View full text |Cite
|
Sign up to set email alerts
|

Implant osseointegration in irradiated bone: an experimental study

Abstract: The present study showed that both the bone volume and BIC were higher in the control group. However, the failure rates of the implants were low in both irradiated groups. The PRP was a positive adjuvant in the osseointegration process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The denser peri-implant bone of nanomodified SLM implants than untreated SLM and TixOs implants might contribute to strengthening the bone-to-implant mechanical anchorage. Osteoid was believed as the signal of new bone formation, and the amount of which decreased while new bone becoming mineralized and mature (Stadlinger et al, 2009;Ocana et al, 2017). We found less osteoid beside nanomodified SLM implants than untreated SLM implants at 2 weeks.…”
Section: Discussionmentioning
confidence: 60%
“…The denser peri-implant bone of nanomodified SLM implants than untreated SLM and TixOs implants might contribute to strengthening the bone-to-implant mechanical anchorage. Osteoid was believed as the signal of new bone formation, and the amount of which decreased while new bone becoming mineralized and mature (Stadlinger et al, 2009;Ocana et al, 2017). We found less osteoid beside nanomodified SLM implants than untreated SLM implants at 2 weeks.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, our results also showed a high success rate both in experimental groups and control groups. However, the conclusion is based on the condition that the radiation dose is lower than 55 Gy and there is no force loading on titanium implants [8, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The key to the success of titanium implant is based on the osseointegration of bone and titanium implant, which could be seriously affected by radiation. Studies showed that the BIC was reduced significantly in irradiated bone [27, 28]. At 16 weeks after implant surgery, a 28% BIC was found in irradiated mandibles compared to 69% in nonirradiated mandibles [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These implant materials are usually used in the form of either disc [ 10 , 11 , 12 ] or cylinders [ 13 , 14 ] to determine the alteration in cell behavior by exploring various parameters, such as type of metal [ 15 ], surface roughness [ 16 ], and sterilization techniques [ 17 , 18 ]. Conversely, the source of stem cells can also influence cell response.…”
Section: Introductionmentioning
confidence: 99%